Body Composition Asymmetries in University Ice Hockey Players and Their Implications for Lower Back Pain and Leg Injury. Issue 10 (8th October 2022) - Resta, Tiziana; Frenette, Stephane; Rizk, Amanda; Fortin, Maryse
Abstract: Resta, T, Frenette, S, Rizk, A, and Fortin, M. Body composition asymmetries in university ice hockey players and their implications for lower back pain and leg injury. J Strength Cond Res 36(10): 2830–2836, 2022—Right to left asymmetries in body composition have been examined across many sports, suggesting possible implications for lower back pain (LBP) and decreased level of performance. However, we are not aware of any study that has examined the presence and implications of morphological asymmetries in ice hockey players. The purpose of this study was to (a) investigate body composition asymmetries in female and male university-level ice hockey players and (b) examine whether the degree of body composition asymmetry is associated with the history of LBP and lower-limb injury (LLI). A total of 32 players (female = 18, male = 14) were included in this cross-sectional study (e.g., university research center setting). Dual-energy X-ray absorptiometry (DEXA) was used to acquire body composition measurements. The parameters of interest included bone mass, lean body mass, and fat mass, for the right and left sides and body segments (e.g., arm, leg, trunk, and total), separately. The history of LBP and LLI was obtained using a self-reported demographic questionnaire. The statistical significance for the study was set at p < 0.05. Our findings revealed significant side-to-side asymmetry in arm and total bone mass in females, with higher values on the right side. Both males and females also had significantly greater trunk lean body mass on the left side. With the exception of greater arm bone mass asymmetry being associated with LBP in the past 3 months, there was no other significant association between the degree of asymmetry with LBP and LLI. This study provides novel data regarding the presence of asymmetry in body composition in university-level ice hockey players. Monitoring body composition in athletes provides information that can be used by athletic trainers and strength and conditioning coaches to develop injury prevention, performance optimization, and targeted rehabilitation programs.